2010
DOI: 10.1371/journal.pone.0010106
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of Obesity among HIV-Infected Persons during the HIV Epidemic

Abstract: BackgroundThe prevalence and factors associated with overweight/obesity among human immunodeficiency virus (HIV)-infected persons are unknown.MethodsWe evaluated prospective data from a U.S. Military HIV Natural History Study (1985–2004) consisting of early diagnosed patients. Statistics included multivariate linear regression and longitudinal linear mixed effects models.ResultsOf 1682 patients, 2% were underweight, 37% were overweight, and 9% were obese at HIV diagnosis. Multivariate predictors of a higher bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
210
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(236 citation statements)
references
References 40 publications
20
210
6
Order By: Relevance
“…The focus on medically appropriate food assistance embodied by Food = Medicine and other similar interventions is especially salient given the need to address concurrent food insecurity and obesity in chronically ill populations. HIV-specific food assistance in resourcepoor settings is generally tailored for underweight populations, although treated populations with HIV increasingly have higher BMIs [48,49]. We previously showed that providing energy-dense forms of food assistance to overweight or obese, food-insecure individuals with treated HIV infection leads to weight gain [50], increasing the risk for chronic comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on medically appropriate food assistance embodied by Food = Medicine and other similar interventions is especially salient given the need to address concurrent food insecurity and obesity in chronically ill populations. HIV-specific food assistance in resourcepoor settings is generally tailored for underweight populations, although treated populations with HIV increasingly have higher BMIs [48,49]. We previously showed that providing energy-dense forms of food assistance to overweight or obese, food-insecure individuals with treated HIV infection leads to weight gain [50], increasing the risk for chronic comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosed at antenatal screening in 2007, she had been on HAART for four years with a suppressed viral load (less than 34 copies per ml) and CD4 count of 680 cells/ mm 3 at the time of surgery. Prior to surgery, she lost 26 kg through a combination of diet and exercise; however, her weight had stabilised at 154 kg.…”
Section: Case Reportmentioning
confidence: 99%
“…1 Obesity in HIV is a worrying trend with highly active antiretroviral therapy (HAART) independently associated with metabolic syndrome. 2,3 Bariatric surgery has been shown to be more effective than conservative measures in the remission of metabolic syndrome. 4 So far little research has been done looking at bariatric surgery in HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with reduced plasma adiponectin levels, and rates of obesity are increasing among HIV-infected persons [45,46]. Further, HIV patients are predisposed to lipodystrophy, likely an effect of both HIV itself and antiretroviral agents [17,47].…”
Section: Discussionmentioning
confidence: 99%